2020
DOI: 10.3389/fmed.2020.00188
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus: A Troll in the ICU? Overview of the Literature and Perspectives for the Future

Abstract: Cytomegalovirus (CMV) is one of the most pathogenic viruses in human. After a primary infection, CMV resides in the host for life as a latent infection. When immunity is reduced, CMV can escape the suppressive effects of the immune system and lead to viremia and antigenemia. This reactivation, first seen in transplant patients, has also been documented in non-immunocompromised CMV-seropositive critically ill patients and is associated with higher morbidity and mortality. In the latter, it is not clear whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 82 publications
1
46
0
1
Order By: Relevance
“…The strict relation between immunosuppression and reactivation of latent viruses and an increased prevalence of opportunistic viral infections is well known, especially in transplanted patients and in ICU patients ( Fishman, 2013 , Schildermans and De Vlieger, 2020 , Limaye and Boeckh, 2010 , Frantzeskaki et al, 2015 , Ong et al, 2017 , Cantan et al, 2019 , Coşkun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strict relation between immunosuppression and reactivation of latent viruses and an increased prevalence of opportunistic viral infections is well known, especially in transplanted patients and in ICU patients ( Fishman, 2013 , Schildermans and De Vlieger, 2020 , Limaye and Boeckh, 2010 , Frantzeskaki et al, 2015 , Ong et al, 2017 , Cantan et al, 2019 , Coşkun et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 influence on immunological response, and its relationship with the reactivation of opportunistic viral infection in the clinical course of COVID-19 is still under investigation. Among various pathogens, opportunistic viral infections such as human cytomegalovirus (HCMV) and Epstein-Barr virus (EBV) are particularly relevant in immunocompromised patients ( Fishman, 2017 , Fishman, 2013 ) and their reactivation has also been reported in patients in intensive care units (ICU) with no previous immune suppression ( Schildermans and De Vlieger, 2020 , Limaye and Boeckh, 2010 , Frantzeskaki et al, 2015 , Ong et al, 2017 , Cantan et al, 2019 , Coşkun et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CMV reactivation on adverse clinical outcomes in immunocompetent critically patients have been associated with higher blood viral loads ( 208 ). Although no studies have robustly responded to whether and when CMV reactivation should be treated in this patient population ( 209 ), it has been suggested that therapy should be administered if CMV reactivation is associated with organ-involvement and/or if high viral loads are detected (≥10 3 copies/mL) ( 208 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Two randomized controlled trials assessing the use of prophylactic or preemptive treatment with aciclovir for HSV reactivation in mechanically ventilated patients, found that aciclovir administration did not improve clinical outcomes ( 207 ). As for HSV, two randomized controlled studies (the GRAIL-trial and the CCCC-trial) evaluating the efficacy of preemptive treatment for CMV reactivation in seropositive patients, failed to show benefit in IL-6 levels changes and in clinical outcomes, respectively ( 209 211 ). The GRAIL-trial, however, demonstrated that ganciclovir group had significantly more ventilator-free days in the sepsis subgroup analysis ( 209 , 211 ).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation